Characteristic and human exposure risk assessment of per- and polyfluoroalkyl substances: A study based on indoor dust and drinking water in China. (November 2019) - Ao, Junjie; Yuan, Tao; Xia, Hui; Ma, Yuning; Shen, Zhemin; Shi, Rong; Tian, Ying; Zhang, Jun; Ding, Wenjin; Gao, Li; Zhao, Xiaodong; Yu, Xiaodan
Abstract: Per- and polyfluoroalkyl Substances (PFAS) are ubiquitous in the environmental matrix, and their eco-toxicity on wide life and health risks on humans arising concerns. Due to the information gap, current risk assessments of PFAS ignore the indoor exposure pathway such as indoor dust and the different sources of drinking water. We collected and analyzed 168 indoor dust and 27 drinking water samples (including tap water, filtered water and bottled water). The mean concentrations of six typical PFAS measured in indoor dust and drinking water are in the range of 15.13–491.07 ng g −1 and 0.31–4.14 ng L −1, respectively. For drinking water, PFOA and PFOS were the dominant compounds, while PFHxS was the most abundant in indoor dust. Short-chain PFAS concentrations were higher than long-chain PFAS in both drinking water and indoor dust. Higher concentration of PFAS was observed in tap water and filtered water than bottled water. The total daily intake (TDI) of six PFAS are 20.67–52.97 ng kg −1 d −1 for infants, children, teenagers, and adults. As to children, teenagers, and adults, perfluorooctanoate (PFOA) is the major compound, accounting for 72.9–74.7% of the total daily intake. And PFOA (38.7%) and perfluorooctane sulfonate (PFOS, 42.2%) are the dominant PFAS for infants. The quantitative proportions of exposure sources are firstly revealed in this study, which in the order of foodstuff > indoor dust > drinking water > indoor air. Although the contribution to the PFAS intake of drinking water and indoor dust was not predominant (<9%), the health risks caused by long-term exposure need our attention. The hazard quotient (HQ) values of total PFAS were in the range of 0.154–0.498, which suggesting the relatively lower exposure risk in Chinese population. This study provides important reference to understand PFAS exposure status other than foodstuff. Graphical abstract: Image 1 Highlights: Short-chain PFAS concentrations were higher in drinking water and indoor dust. Both PFOA and PFOS are the dominant PFAS for infants. Indoor dust and drinking water contribute about 9% of total PFAS exposure. PFAS average daily intakes sort as foodstuff > indoor dust > drinking water > indoor air. Abstract : Capsule: Pollution characteristics and daily intakes of PFAS from indoor dust and drinking water were quantitively investigated in different age groups of general population.